POLA KOMUNIKASI KOMUNITAS CYCLING POSER DALAM MEREKRUT ANGGOTA BARU - Putra, Arya Giri; Sekar Wangi, Maya; Maserona Sarungu, Lukas (Solidaritas, 2024)
ABSTRACT The Cycling Poser Community is a bicycle community originating from Solo. This community was founded by Angga Septian Hari Wibowo and Annaz Fauzan in 2020. It was founded to preserve cycling culture in the city of Solo, apart from that, the existence of work from home made Angga and Annaz look for activities related to sports. In the four years since, the condition of this community has improved, many people already know this community and want to become members of the community. The question arises from the background, what is the communication pattern of the Cycling Poser community in recruiting new members? What are the barriers to recruiting members to this community? On this occasion the researcher used the theory of communication patterns according to Joseph A Devito, this theory has five patterns, namely the circle pattern, wheel pattern, Y pattern, chain pattern and star pattern. This type of research is qualitative with descriptive methods. Data collection techniques were carried out by means of observation, interviews and documentation. The results of this research show that the Cycling Poser community uses a star communication pattern, apart from that there are obstacles that occur, namely, the existence of incompatibility between individuals is the main obstacle in recruiting new members, thus making the founder more extra in establishing friendships and relationships. Keyword: Communication, Communication patterns and the Cycling Poser Community